Radioecological Monitoring of Radionuclides in Natural Waters of Sherabad River, Surkhandarya Region (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents studies on the radiometric determination of the beta-radiation activity of radionuclides of potassium-40 and thorium-232 isotopes in the waters of the Sherabad River in the Surkhandarya region. Six samples were taken from the water of the Sherabad River and measured with a radiometer-spectrometer MKGB01. The concentration of potassium-40 and thorium-232 isotopes in a sample taken from a river flowing near the village of Kallamozor was higher than at other points.